If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 31x + -31(1 + -1x) = 0 31x + (1 * -31 + -1x * -31) = 0 31x + (-31 + 31x) = 0 Reorder the terms: -31 + 31x + 31x = 0 Combine like terms: 31x + 31x = 62x -31 + 62x = 0 Solving -31 + 62x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '31' to each side of the equation. -31 + 31 + 62x = 0 + 31 Combine like terms: -31 + 31 = 0 0 + 62x = 0 + 31 62x = 0 + 31 Combine like terms: 0 + 31 = 31 62x = 31 Divide each side by '62'. x = 0.5 Simplifying x = 0.5
| 5x+0.40x=0.30(x+5) | | 5y+3=-6y+4+12 | | (5x+1)(x-5)=0 | | -2+5x+7x^2=0 | | .5(4-2x)=-6 | | -5x-5=-45 | | -42=-2(1+4n) | | 2X-1=21 | | 2a^2+16a^2+30a= | | -1-2p=-5 | | (v+3)(5v-3)=0 | | k-4=15 | | -4x-2=-34 | | -4(r-4)=44 | | 2a+6-6a=2 | | x(x+4)-6(x+4)= | | 3=-y+4 | | -2k-5=-5 | | 2n^2+4n+4=0 | | 2-3b=20 | | -3=-y+4 | | -3+2k=-19 | | 3(k-2)=24 | | 5x+42=132 | | 8=2+b+3 | | 5-3m=11 | | 12x+131=189+3x | | -16=p-6 | | X+37=46 | | 2(n+3)=2 | | 5m+6m+2+4m+8+3m=82 | | -4-2m=12 |